A mathematical SSCM model for minimizing the CO2 emission with considering economic goals and social benefits - Ravand, Zahra Ghorbani; Qi, Xu (Archives of Business Research, 2018)
Nowadays the main problem in the world is environmental pollution. One of the main sources which impact on the environment is Industrial factories. In this regards, we define a mathematical model for finding a solution for minimizing CO2 emission. According to SSCM model, we define three objective functions: 1- minimize CO2 emission which are coming from SCM Process, 2- maximizing profit 3- Maximizing social benefits. For details, first, we define decision variables in the SCM process, second, we normalize the variables with using fuzzy logic algorithm, third we set the objective functions accordingly, and finally we define constraints with considering Carbon Credit, Demands, Production rates, Investment, numbers of Jobs and value added. For implementation and case study, considering two factories, four kind of products in the variety of EFP-UEFP range, gathering their data and implement the model accordingly. After solving, we do sensitive analysis for finding other solutions, then we define a degree for EFP-EUFP range that we can measure EFP degree for products by Likert Scale. We found that in addition to government limitations, demand quantities should be changed by customers.